Alcohol consumption and coping strategies in university students. Empirical Study - Moysén Chimal, Alejandra (2014)
Alcohol consumption rates in men and women have similar values, butan increase in women’scase is observed(NAS*, 2002, 2008).Also drinking alcoholic beverages has been associated with coping strategies. Not having ways of coping with stressgenerated by stress management problems generally ends up in alcohol consumption. The sample of this study was made up of 1800 university students, 44.8% men and 55.2% women, aged 22 on average. COPE was applied to them for measuring coping strategies and three questions were made to classify alcohol consumption. The results show that 72.3% of students consume alcohol, being men withhigher consumption; it is also observed that women face stress mainly with religious support, while men resort toevasion, alcohol and drugconsumption, and humor.